2009
DOI: 10.1074/jbc.m109.019257
|View full text |Cite
|
Sign up to set email alerts
|

Succination of Thiol Groups in Adipose Tissue Proteins in Diabetes

Abstract: S-(2-SuccinylWe show here that succination of protein is also increased in epididymal, mesenteric, and subcutaneous adipose tissue of diabetic (db/db) mice and that adiponectin is a major target for succination in both adipocytes and adipose tissue. Cys-39, which is involved in cross-linking of adiponectin monomers to form trimers, was identified as a key site of succination of adiponectin in adipocytes. 2SC was detected on two of seven monomeric forms of adiponectin immunoprecipitated from adipocytes and epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 34 publications
1
58
0
Order By: Relevance
“…Concomitant with a decrease in p-eIF2α levels, there was a pronounced increase in CHOP, a terminal marker of ER stress, but only in adipocytes matured in 30 mM glucose (Figure 2A&E). Consistent with previous results (Nagai 2007, Frizzell 2009), protein succination increases in adipocytes matured in 30 mM glucose for up to 8 days (M2-M8, lanes 8-23) and interestingly appears to increase in parallel with CHOP levels (Figure 2A). In addition to the observed decrease in intracellular adiponectin, the adipocytes matured in 30 mM glucose secreted increased levels of pro-inflammatory cytokines including TNFα, VEGF and MCP-1 (Figure 2F-G).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Concomitant with a decrease in p-eIF2α levels, there was a pronounced increase in CHOP, a terminal marker of ER stress, but only in adipocytes matured in 30 mM glucose (Figure 2A&E). Consistent with previous results (Nagai 2007, Frizzell 2009), protein succination increases in adipocytes matured in 30 mM glucose for up to 8 days (M2-M8, lanes 8-23) and interestingly appears to increase in parallel with CHOP levels (Figure 2A). In addition to the observed decrease in intracellular adiponectin, the adipocytes matured in 30 mM glucose secreted increased levels of pro-inflammatory cytokines including TNFα, VEGF and MCP-1 (Figure 2F-G).…”
Section: Resultssupporting
confidence: 92%
“…We have identified ∼40 succinated proteins in adipocytes (Merkley 2013, Nagai 2007, Piroli 2014,) and we have demonstrated that succination appears to impair protein function or regulation, e.g. increased succination of adiponectin in the presence of high glucose can reduce the polymerization and secretion of this adipokine (Frizzell 2009). Interestingly we have observed that several endoplasmic reticulum (ER) proteins, including the oxidoreductase protein disulfide isomerase (PDI), are succinated in the adipocyte during diabetes (Nagai 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Isoelectric focusing on pI 4-7 11 cm and 17 cm strips or narrow range 4.7-5.9 11 cm strips and two-dimensional (2D) gel electrophoresis was performed as described previously [3]. The 2D gels were stained for protein using Sypro Ruby total protein stain (Invitrogen, Grand Island, NY) [3] or transferred onto PVDF membrane to detect protein succination by western blotting.…”
Section: Methodsmentioning
confidence: 99%
“…The 2D gels were stained for protein using Sypro Ruby total protein stain (Invitrogen, Grand Island, NY) [3] or transferred onto PVDF membrane to detect protein succination by western blotting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation